An Overview of Waste Milk Feeding Effect on Growth Performance, Metabolism, Antioxidant Status and Immunity of Dairy Calves - Ma, Yulin; Khan, Muhammad Zahoor; Xiao, Jianxin; Alugongo, Gibson Maswayi; Chen, Xu; Li, Shengli; Wang, Yajing; Cao, Zhijun (Frontiers in Veterinary Science, 2022)
Waste milk (WM) is a part of the milk produced on dairy farms, which is usually unsuitable for human consumption. The WM contains transition milk, mastitis milk, colostrum, milk with somatic cells, blood (Hemolactia), harmful pathogens, pathogenic and antibiotic residues. Due to the high cost of milk replacer (MR), dairy farmers prefer raw WM to feed their calves. It has been well established that WM has a greater nutritive value than MR. Hence WM can contribute to improved growth, rumen development, and immune-associated parameters when fed to dairy calves. However, feeding raw WM before weaning has continuously raised some critical concerns. The pathogenic load and antibiotic residues in raw WM may increase the risk of diseases and antibacterial resistance in calves. Thus, pasteurization has been recommended as an effective method to decrease the risk of diseases in calves by killing/inhibiting the pathogenic microorganisms in the raw WM. Altogether, the current review provides a brief overview of the interplay between the positive role of raw WM in the overall performance of dairy calves, limitations of raw WM as a feed source and how to overcome these issues arising from feeding raw WM.